Spray Dried Levodopa-Doped Powder Potentially for Intranasal Delivery - Xuan Liu; Shen Yan; Mengyuan Li; Shengyu Zhang; Gang Guo; Quanyi Yin; Zhenbo Tong; Xiao Dong Chen; Winston Duo Wu (MDPI AG, 2022)
This work was aimed to develop levodopa (L-dopa) nasal powder to achieve controllable drug release and high nasal deposition efficiency. A series of uniform microparticles, composed of amorphous L-dopa and excipients of hydroxypropyl methyl cellulose (HPMC), polyvinylpyrrolidone (PVP), or hydroxypropyl-β-cyclodextrin (CD), were fabricated by a self-designed micro-fluidic spray dryer. The effects of excipient type and drug/excipient mass ratio on the particle size, morphology, density, and crystal property, as well as the in vitro performance of drug release, mucoadhesion, and nasal deposition, were investigated. Increased amounts of added excipient, regardless of its type, could accelerate the L-dopa release to different extent. The addition of CD showed the most obvious effect, i.e., ~83% of L-dopa released in 60 min for SD-L1CD2, compared to 37% for raw L-dopa. HPMC could more apparently improve the particle mucoadhesion than PVP and CD, with respective adhesive forces of ~269, 111, and 26 nN for SD-L1H2, -L1P2, and -L1CD2. Nevertheless, the deposition fractions in the olfactory region for such samples were almost the same (~14%), probably ascribable to their quite similar particle aerodynamic diameter (~30 μm). This work demonstrates a feasible methodology for the development of nasal powder.